Do women top managers help women advance? A panel study using EEO-1 records - Fidan Ana Kurtulus; Donald Tomaskovic-Devey (Institute for the Study of Labor (IZA), 2012)
The goal of this study is to examine whether women in the highest levels of firms' management ranks help reduce barriers to women's advancement in the workplace. Using a panel of over 20,000 private-sector firms across all industries and states during 1990-2003 from the U.S. Equal Employment Opportunity Commission, we explore the influence of women in top management on subsequent female representation in lower-level managerial positions in U.S. firms. Our key findings show that an increase in the share of female top managers is associated with subsequent increases in the share of women in mid-level management positions within firms, and this result is robust to controlling for firm size, workforce composition, federal contractor status, firm fixed effects, year fixed effects and industry-specific trends. Moreover, although the influence of women in top management positions is strongest among white women, black, Hispanic and Asian women in top management also have a positive influence on subsequent increases in black, Hispanic and Asian women in mid-level management, respectively. Furthermore, the influence of women in top management positions is stronger among federal contractors, and in firms with larger female labor forces. We also find that the positive influence of women in top leadership positions on managerial gender diversity diminishes over time, suggesting that women at the top play a positive but transitory role in women's career advancement.
urn:nbn:de:101:1-201207127022
Keywords: J16; J21; J24; J44; J62; J71; J78; J82; M51; 330; women managers; gender diversity; race diversity; discrimination; mentoring; promotions; hiring; retention; Weibliche Führungskräfte; Weibliche Arbeitskräfte; Erwerbsverlauf; Mittleres Management; USA